Sistema web de gestión del inventario de equipos en las unidades de docencia, investigación y vinculación de la ESPAM MFL - Álvarez Moreira, Cinthya Pamela (2021)
The work had the intention of developing a web system of equipment inventory management in the teaching, research and entailment units of the ESPAM-MFL to maintain control of their information. To structure, plan and control the system development process, the Agile Extreme Programming (XP) methodology was specified; that ordered the development of systems, for it the 4 phases were used which are: planning, design, coding and testing; the planning phase carried out in a visit to the General Research Coordination in which an interview with the person in charge of the area was needed, in order to obtain the requirements for the web system, in the design phase the database was modeled which in turn was transferred to the SQL Server database manager. After this, we went to the coding phase where the interface code was developed in the Visual Studio tool under the .NET environment in the C # language; it was identified in the user stories that were raised in the first phase. Finally, in the testing phase, the proper functioning of the web solution was verified, as a result it was obtained that the productivity of the processes carried out in each of the UDIVs is more effective, so the implementation and use of the system allowed to control the equipment information of the units and their availability.